Application of a novel chromophoric reagent, 2, 2′-binaphthyl-3, 3′-dicarbonyl cyanide, to the absolute configuration determination of chiral secondary alcohols. Issue 24 (11th June 2020) - Fujiwara, Toshio; Taniguchi, Yuka; Kokuryu, Yuri; Baba, Yuumi; Kawano, Daiki; Kawakami, Yuuki; Suzuki, Shouta; Katsumoto, Yukiteru; Ozeki, Minoru; Iwasaki, Hiroki; Takahashi, Ichiro; Kojima, Naoto; et al.
Graphical abstract: Highlights: The method applicable to determining absolute configuration. The method based on induced circular dichroism. New agent more effective than other ones in determination of absolute stereochemistry. X-ray analysis and 1 H NMR measurement support structure of the binaphthyl esters. Powerful tool for practical microanalysis. Abstract: 2, 2′-Binaphthyl-3, 3′-dicarbonyl cyanide possessing two reaction sites was designed and synthesized as a new chromophoric reagent for exciton-coupled circular dichroism (ECCD), which is more effective in determination of the absolute stereochemistry of the target chiral alcohols than 2, 2′-binaphthyl-3-methoxycarbonyl-3′-carbonyl cyanide, which contains only one reaction site. The CD spectra of the 2, 2′-binaphthyl diesters derived from chiral secondary alcohols show bisignate curves centered at 240 nm, of which the Δε value was roughly twice as large as that of the binaphthyl methyl monoester.